Globalization Dimensions and Poverty Dynamics in Indonesia: Evidence from a Vector Error Correction Model (VECM) - Qurrota Ayu Nindien; Arivina Ratih Yulihar Taher; Asih Murwiati; I Wayan Suparta; Neli Aida (Lafadz Jaya Publisher, 2025)
This study investigates the long-run and short-run relationships between globalization dimensions, economic growth, income inequality, and poverty in Indonesia. While globalization is widely considered a driver of economic development, its impact on poverty remains theoretically ambiguous and empirically mixed, particularly in developing countries. This study addresses this gap by examining multiple dimensions of globalization—economic globalization, social globalization, and economic cooperation—within a unified econometric framework. Using annual time series data from 1984 to 2020, this study employs the Vector Error Correction Model (VECM) to capture both short-term dynamics and long-term equilibrium relationships among variables. The results confirm the existence of cointegration, indicating a stable long-run relationship between poverty and its determinants. In the long run, economic growth, economic globalization, social globalization, and economic cooperation are found to significantly reduce poverty. In contrast, income inequality has a positive and statistically significant effect, suggesting that unequal income distribution remains a key structural barrier to poverty reduction. However, the short-run results reveal that none of the explanatory variables significantly influence poverty, highlighting the delayed transmission mechanism of globalization and macroeconomic factors. These findings suggest that the benefits of globalization are not immediate but materialize over time through structural transformation processes. From a policy perspective, the study emphasizes that globalization alone is insufficient to alleviate poverty without inclusive growth policies. Reducing inequality, improving human capital, and strengthening sectoral productivity—particularly in agriculture—are essential to ensuring that globalization contributes to sustainable poverty reduction in Indonesia.